PERAN HUBUNGAN MASYARAKAT (HUMAS) DALAM MENJAGA REPUTASI SEKOLAH DI MI HAMALATUL QUR’AN KARAWANG - Diningrum Citraningsih; Robi’atul Adawiyah (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to determine the role of public relations in maintaining the reputation of MI Hamalatul Qur'an Karawang, identifying the supporting and inhibiting factors faced by public relations in maintaining the school's reputation based on facts on the ground. This study uses a descriptive qualitative approach. Data collection techniques use interviews, observation, and documentation methods. Data validity uses source triangulation techniques. Data analysis techniques use the interactive model of Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of the study found that public relations plays a role as a communicator, relationship builder, supporter of management functions, and guardian of the school's reputation. This role is realized through various communication activities directly and through social media. The success of public relations is influenced by several supporting factors, such as effective communication, availability of facilities and infrastructure, community support, quality of human resources, and the ability to handle issues. Inhibiting factors include the lack of public understanding of education and school relationship management, as well as the potential for miscommunication between school residents and the community.